The relationship between knowledge management approaches and job satisfaction in Pejabat Tanah Dan Jajahan Tanah Merah and Pejabat Tanah Dan Jajahan Pasir Mas / Atiela Amran - Amran, Atiela (2015)
The purposed of this study is to investigate the relationship of Knowledge Management and Job Satisfaction in Pejabat Tanah dan Jajahan Tanah Merah and Pejabat Tanah (PTJTM) dan Pejabat Tanah dan Jajahan Pasir Mas (PTJPM). There are about 103 staffs or workers that have been taken as a sample size in this research study. The questionnaires had been distributed to 3 same departments in both organizations which are Administration, Development and Technical Department or Units by using stratified sampling methods. There are five independent variables within this study which were Acquistion, Coversion, Application, Storing and Protection. While there are several findings that have been analyzed which are reliability, descriptive frequencies, descriptive statistics and correlation analysis. Overall, the finding founds that all result are varied in their relationship.